Gili Trawangan's Tourism Landscape: Understanding The Contestation between MSMEs, Government, and Visitors - Wathoni, Abdul Wahid; Mulazid, Ade Sofyan; Suhaimi, Ahmad (Universitas Islam Negeri Madura, 2025)
This study investigates the dynamics of interactions among stakeholders in shaping MSME actors' business orientation in Gili Trawangan regarding acceptance and rejection of halal certification on food and beverage products. Using a qualitative approach and case study method, data were collected through participant observation over two months and in-depth interviews with 18 key informants, including MSME actors, government representatives, and tourists. The study explores how MSME actors' attitudes amid contestation between the government as an institutional stakeholder and tourists as primary stakeholders influence decisions to accept or reject halal certification. Findings show that the dominance of primary stakeholders, namely tourists, is the main factor shaping MSME business orientation, which tends to follow tourists' preferences in offering food and beverage products. Conversely, the government's function as an institutional stakeholder in promoting halal certification is less effective, leading MSMEs to resist certification and rely on traditional halal-based offerings and product diversification into non-halal items to attract various tourist segments. This research contributes significantly to understanding power relations and interests among stakeholders in MSME management within tourism and policy implications related to halal certification. Limitations include geographic scope, focus on certain MSME groups in Gili Trawangan, and reliance on data subjectively reported by informants. Future research should broaden the context and include diverse MSME groups in different regions to obtain a more comprehensive picture of stakeholder influence on business orientation.